Practice analysis of domestic and foreign industry benchmarking enterprises in the field of network and information security - Xiaoyin XI; Xiaoyun YUAN (Dianxin kexue)
In order to better promote the construction of China Telecom’s network and information security governance system,optimize the network and information security product service system,and promote the cultivation and development of network and information security core competence,domestic and foreign industry benchmark enterprises were selected to carry out practical case analysis.The advanced successful experience of benchmarking enterprises in the field of network and information security were summarized,and the current development status and future development trend in the field of network and information security were further combined,and targeted development suggestions and measures were put forward to improve the governance system of China’s telecommunications network and information security,improve the governance ability,as well as related business,and the development of products and services provides useful help.